Transformasi Materi Bahan Ajar Pendidikan Agama Islam dari Metode Konvensional ke Format Digital - Ahmad Dawam Zaki Fuadi Albasami; Mustadi Mustadi; Abdul Basir (Pascasarjana Universitas Qomaruddin, 2024)
This research is motivated by developments in the times where almost everyone has applied technology in their daily lives. Nowadays, technology is used in almost all aspects of education. One of them is at Madrasah Ibtidaiyah Al Hikmah Masangan Bungah. This institution heavily utilizes technology to enhance its educational activities. Some teachers are already proficient in teaching using technology-based learning media. However, some teachers still rely on traditional learning media. Of course, this is less able to increase students' learning motivation, and learning activities tend to be less effective. The aim of this research is to develop conventional Islamic religious education teaching materials into digital ones. In addition, the research aims to evaluate the effectiveness of the teaching materials, based on assessments from media (IT) experts, material experts, and subject teachers. This research model employs a qualitative approach to research and development. The ADDIE model (analysis, design, development, implementation, and evaluation) serves as the research design. The data collection techniques used questionnaires, observations, and field notes, while the data analysis techniques are descriptive-qualitative, where the data source comes from the learning process. The results of this research are 1) Islamic Religious Education Teaching Materials that are suiTabel for class 5 in the form of learning videos that focus on the material